A novel missense variant in cathepsin C gene leads to PLS in a Chinese patient: A case report and literature review - Hui Yu; Xun He; Xiangqin Liu; Houbin Zhang; Zhu Shen; Yi Shi; Xiaoqi Liu (Molecular Genetics & Genomic Medicine, 2021)
Abstract Background Papilon‐Lefevre syndrome (PLS; OMIM 245000) is a rare autosomal recessive disease characterized by aggressive periodontitis and palmoplantar keratoderma. The prevalence of PLS in the general population is one to four cases per million. Although the etiology and pathogenic mechanisms underlying PLS remain largely unclear, existing evidence shows loss‐of‐function mutations of the cathepsin C gene (CTSC; OMIM 602365) could cause PLS. Here we found a novel variant of the CTSC gene in a Chinese PLS family and predicted the effect of the variant on the physic–chemical characters and tertiary structure of the protein. Methods The 1–7 coding exons and exon–intron boundaries of CTSC gene of the proband and her family were amplified and sequenced directly, and Chromas was used to read sequencing files. Furthermore, the PolyPhen‐2, PROVEAN, and Mutation Taster were utilized to predict the pathogenicity of the variant. Besides, the physic–chemical and structural characters of the protein were analyzed by ProtParam, ProtScale, and SWISS‐MODEL. Results Our study identified a novel homozygous variant c.763T>C (p.Cys255Arg) in exon 6 of the CTSC gene, and it was a likely pathogenic variant as predicted by PolyPhen‐2, PROVEAN, and Mutation Taster. Moreover, ProtParam and Protscale revealed the variant increased the isoelectric point and hydrophilicity of the protein, and the SWISS‐MODEL analysis suggested the variant was located in a critical domain for protein activity. Conclusion Our study analyzed a Chinese family with PLS and identified a novel missense variant in the CTSC gene. Besides, this study retrospectively summarized 113 variants of CTSC in the world and highlighted the features of 27 CTSC variants in Chinese PLS patients. In addition, this study paid much particular attention to the relationship between CTSC variants and different phenotypes.